Nature of TVET Lecturer Learning During Work Integrated Learning: A South African Perspective - Mesuwini, Joseph; Thaba-Nkadimene, Kgomotlokoa Linda; Kgomotlokoa, Linda (Journal of Technical Education and Training, 2021)
The purpose of the study was to explore Technical Vocational Education and Training (TVET) lecturers learning through Work Integrated Learning (WIL), specifically to establish the nature of their learning and determine how the lecturers understood their learning. However, since the launch of this WIL initiative, what these lecturers learnt, and how they understand their learning has not been researched. This study sought to investigate the nature of learning of these lecturers. The study was conducted in three TVET colleges in KwaZulu-Natal (KZN) province. Kolb’s experiential learning theory was used to undergird the study. The research was located in the interpretive paradigm, which used a multiple case study design. A qualitative research approach was adopted. Convenience sampling design was used to select three TVET colleges as well as industries hosting WIL lecturers. Eighteen TVET lecturers were purposively sampled from a population of lecturers in the three TVET colleges. Data were generated using semi-structured face-to-face interviews from lecturers who completed WIL and those who were on WIL during the study. The study used thematic and narrative analysis to analyse data. Findings revealed that lecturers gained practical experiences through teamwork, networking and sharing of experiences and ideas with industry personnel, diagnosis, troubleshooting, and repairing engineering components during WIL. The study recommended capacitating all TVET lecturers with practical industry skills. The findings showed that TVET lecturers did not simply go to an industry site and pick up new experiences from their practice but learnt from others. Recommendations from the study informed the discussions and policy decisions in the Department of Higher Education and Training (DHET), Swiss-South African Cooperation Initiative (SSACI) and Sector Education and Training Authority (SETA) on this WIL initiative, and may influence provision of other forms of support necessary for the TVET sector.